Myth, History and marvelous in the gesture of the Banu Hillal - SOUAMES, Amira (Journal of Social Sciences and Humanities, 2023)
The purpose of this communication is to understand the relationship between myth and history in the gesture of the Banu Hillal as told and lived in the east and south of Algeria. As part of a broader study, this analysis will be presented as a general approach to these fragmented stories, this approach is intended above all to propose points of reflection on a form of mythification of history and to lay the groundwork for a re-reading of the so-called theory of the «hillalien catastrophe». In this structure, therefore, going from the collective to the individual, there is also a reduction which, ending with a song, transforms the warrior couple into a loving couple. And the collective adherence to this new hymn to life appears in the refrains, a questioning to which the audience responds with social recognition which gives this re-reading of History the force of a mythical saying. The fundamental question is there: the game of desacralization of the collective makes it possible to no longer maintain coercive relations with the founding story and we are perhaps witnessing a new type of relationship to these stories, a relationship characterized by a dilution from the epic to the marvelous. The gesture of the Banu Hillal, far from favoring fighting, poses the primacy of dialogue as a source of development of creative contacts. The desecration of the collective will make it possible to no longer maintain coercive relations with the founding narrative and we are perhaps witnessing a new type of relation to these stories, characterized by a dilution of the epic in the marvelous.